Gambaran Interaksi Caring Perawat dengan Pasien: Studi Pendahuluan - Dina Ayu Mentari; Sarah Ulliya (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Introduction: In nursing practice nurses often show less optimal caring interactions because they have overload tasks. The purpose of this study was to describe the caring interactions between nurses and patients.Methods: This study was a descriptive study with a survey approach. The samples were 89 nurses at the inpatient wards who were recruited using purposive sampling technique. The data were collected using the Caring Nurse-Patient Interactions (CNPI-23N) tool and analyzed using a univariate analysis presented in the form of the frequency distribution.Results: The results showed that 84.3% of caring interactions between nurses and patients were good, and the remaining 18.7% were adequate. The dimension of comforting care achieved the highest value in which all respondents (100%) were at a good level. Meanwhile, the dimension of humanistic care achieved the lowest value in which 38.2% of respondents were at an adequate level.Conclusion: This study concluded that the caring interactions between nurses and patients had been well implemented. It is expected that the nursing profession and the hospital management maintain the quality of nursing care and increase the knowledge and training.